Computed tomography scan findings in eclampsia: a prospective study - Rajeswari, K. S. Raja; Niranjana, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Eclampsia is a leading cause of maternal death, with classical neurological symptoms that include headache, nausea, vomiting, cortical blindness, coma and convulsions. Computed tomography (CT) scan helps in diagnosing and management of eclampsia in pregnant women. The present study was done with the objective to analyse the findings of CT scan of brain in eclampsia, to identify the prevalence of neurovascular complications in these cases and to determine if these findings can be of value in determining the prognosis of this disorder. Methods: This was a prospective study done on 100 patients with eclampsia. All of the 100 patients were screened with CT scan brain at Institute of Obstetrics and Gynaecology, Egmore, Chennai during the period from August 2008 to August 2009. All the data were analyzed and compared between the groups of positive CT scan and negative CT scan observations. Results: Out of 100 patients, positive CT scan findings were noticed in 15 patients. Of them, 7 patients expired, and 8 patients survived after treatment. Of the expired patients (7), 5 of them expired due to brain haemorrhage, and 1 patient died with cerebral oedema and 1 with brain infarction. Cerebral odema (46%) was the most common positive CT finding. Parietal region of brain was the most common (40%) affected area. Conclusions: CT scan of brain provides valuable information in determining the prognosis and the prevalence of neurovascular complications in Eclampsia.